Detecting Earnings Management in The Reporting of Nigerian Banks: The Distribution of Ratios Approach (Journal of Governance Risk Management Compliance and Sustainability, 2023)
Earnings management (EM) practice has raised concerns amongst different stakeholders. Analysing financial reports to detect anomalies aims to reduce associated risks to earnings manipulations and safeguard investors’ funds. This study verifies two main issues (a) whether annual reports of the Deposit Money Banks [DMBs] reflect evidence of EM and (b) whether the DMBs engage in more manipulations in periods ‘After’ mandatory adoption of IFRS relative to ‘Prior’ IFRS periods. The study involves all 19 DMBs in Nigeria, but the established selection criteria constrained the final sample to 17 banks. The final sample comprises 319 observations for each bank-ratio form. We compute 14 bank-specific ‘earnings’ ratios for the different years from 2001 to 2020, obtain the distribution of ratios and estimate the Kolmogorov-Smirnov statistics to address two issues. The finding confirms endemic EM but that the manipulations are not consistently a yearly phenomenon. The evidence supposes more EM for the banks' financials prior- relative to the post-IFRS adoption. The evidence supposes implications for banks to attenuate earnings misreporting. We offer those bank supervisory agencies should ensure appropriate monitoring and engagement of officials during the reporting of bank financial records to circumvent opportunistic misreporting.